Language situation in Tatarstan and Turkey - Mardanova, Zalida M.; Kirillova, Zoya N.; Alkaya, Ercan (Modern Journal Language Teaching Methods, 2018)
This work is devoted to the study of the language situation in Tatarstan and Turkey in the conditions of the multinational population of the republics. To achieve this goal, the essence of the notion language situation was revealed, the features of the language situation in Tatarstan and Turkey before the beginning of the 20th century were defined, the language situation of Tatarstan in the 1920s-1930s and 1990-2018s was studied, and a review of the language situation in Turkey after the Kemalist revolution of 1918-1923 until today was made. The authors concluded that the linguistic situation is continuously associated with geopolitical, sociocultural and globalization transformations that influence its structure; the functional potential of the Tatar language is influenced by the language policy, the language situation and the education system; the study of the experience of the Turkish language situation in the historical aspect and the selection of the main development trends allow us to adequately assess the level of language processes in the Republic of Turkey. We made a conclusion that language situations in the Republic of Tatarstan and the Republic of Turkey have significant differences due to the different historical, political, socio-cultural and other features of the development of each region.
Keywords: language situation; language policy; Tatarstan; Turkey; Tatar language; Turkish language